PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS PROBLEM BASED LEARNING (PBL) MENGGUNAKAN APLIKASI ARTICULATE STORYLINE PADA MATERI IKATAN KIMIA - Rati F; Salastri Rohiat; Elvinawati Elvinawati (University of Bengkulu, 2022)
This study aims to determine the level of feasibility and student response to interactive multimedia learning based on problem based learning (PBL) using the articulate storyline application on the chemical bonding material developed. This research is a research and development conducted in March-August 2021. The development model used is the Four-D (4-D) development model which is limited to the define stage, design stage and develop stage. This research was conducted at Bengkulu University and at SMA Negeri 3 Bengkulu City. The study was only conducted on a small scale (limited) trial with a research sample of 32 students taken from class X MIPA 3. The data in the study were obtained from interviews, student needs questionnaires, validation sheets and student response questionnaires. The results of the validation test obtained an average of media validation and material validation of 86% and 89% which were in the range of 81%-100% with very valid criteria. While the student response test obtained a score of 80% which was in the range of 61% -80% with a good category. Based on the results of the validation and the results of the student responses, it can be concluded that interactive multimedia learning based on problem based learning (PBL) using the articulate storyline application on chemical bonding material is declared feasible and can be used as a medium and learning resource for students.